Intracellular PRRs Activation in Targeting the Immune Response Against Fungal Infections - Jannuzzi, Grasielle Pereira; de Almeida, José Roberto Fogaça; Paulo, Larissa Neves Monteiro; de Almeida, Sandro Rogério; Ferreira, Karen Spadari (Frontiers in Cellular and Infection Microbiology, 2020)
The immune response against fungal infections is complex and exhibits several factors involving innate elements that participate in the interaction with the fungus. The innate immune system developed pattern recognition receptors that recognize different pathogen-associated molecular patterns present both on the surface of the fungi cell wall and on their genetic material. These receptors have the function of activating the innate immune response and regulating a subsequent adaptive immune response. Among pattern recognition receptors, the family of Toll-like receptors and C-type lectin receptors are the best described and characterized, they act directly in the recognition of pathogen-associated molecular patterns expressed on the wall of the fungus and consequently in directing the immune response. In recent years, the role of intracellular pattern recognition receptors (TLR3, TLR7, TLR8, and TLR9) has become increasingly important in the pathophysiology of some mycoses, as paracoccidioidomycosis, cryptococcosis, aspergillosis, and candidiasis. The recognition of nucleic acids performed by these receptors can be essential for the control of some fungal infections, as they can be harmful to others. Therefore, this review focuses on highlighting the role played by intracellular pattern recognition receptors both in controlling the infection and in the host's susceptibility against the main fungi of medical relevance.